REQUIREMENT ENGINEERING SISTEM MANAJEMEN ASET GEREJA BERBASIS SOFTWARE AS A SERVICE DAN PROGRESSIVE WEB APPLICATION - Setiyawati, Nina; Bangkalang, Dwi Hosanna; Hartomo, Kristoko Dwi (STKIP PGRI Tulungagung, 2024)
One of the supports for carrying out church service functions is adequate assets. Some of the problems that often arise in handling church assets are: 1) there is no detailed asset data collection; 2) there is no monitoring or notification of regular asset maintenance schedules; 3) there is no monitoring of asset lending. These problems result in changes in asset status, additional assets, and asset movements not being properly documented. Therefore, an asset management system is needed that can manage, control and track assets effectively. In the system development process, the requirements engineering stage is a crucial stage that has a significant influence on the quality of the resulting system. This research focuses on the requirements engineering stages of the church asset management system using the Iterative Requirements Engineering model proposed by Loucopoulos and Karakostas which consists of three stages, namely elicitation, specification, and validation. In the process of exploring solutions based on problem identification, it was discovered that the system needed to be built by implementing software as a service and progressive web application architecture. The validation stage which is carried out using a high fidelity prototype helps potential users understand the real interactions between features in the system.